Tantangan Pemberian Bantuan Luar Negeri Amerika Serikat ke Afghanistan Tahun 2021 - Sahputra, Indra; Agape, Gideon Candra; Anjani P, Dian Ayu; A, Axcel Geraldo; Firmansyah, Q.; Ashari, M. Chusaini (Global and Policy Journal of International Relations, 2022)
ABSTRACTNo less than $145 billion USD has been given to Afghanistan to build governance, economy, socialand societ (SIGAR, 2021). A total of $76.6 billion USD has also been provided through the OfficialDevelopment Aid (ODA) scheme from various countries from 2002 to 2019, not counting anotherbillion dollars coming from International Organizations (Hanke, 2021). However, the HumanDevelopment Report (2020) notes that Afghanistan's Human Development Index (HDI) is still atposition 169 out of 189 countries worldwide, which is a poor performance for this country. Thiscountry is also far from prosperous, even SIGAR classifies Afghanistan as a country that isincreasingly dependent on external aid. In 2021, 43% of Afghanistan's GDP will come from foreignaid, 75% of public spending will come from foreign aid, and 90% of the population lives on less than2 dollars a day. By using a descriptive qualitative method, this paper will answer 2 researchquestions, first regarding the failure and success of US foreign aid to Afghanistan in 2021, secondresearch question is how foreign aid will impact development in Afghanistan in 2021.Key words : Afganistan, International aid, sustainable developmentDOI: https://doi.org/10.33005/jgp.v10i01.3571